Forensic identification of cases with infectious diseases such as novel coronavirus pneumonia - Xin Liu; Wen Liu (Wolters Kluwer Medknow Publications, 2020)
Deaths or other legal disputes caused by novel coronavirus pneumonia (COVID-19) may require forensic pathological autopsy or forensic clinical identification. During daily forensic identification of cases in which individuals died of infectious diseases, forensic identification agencies and experts should be fully aware of the risk of infection when dissecting and examining such cadavers. Furthermore, forensic identification personnel should always adopt effective protective measures. As a novel infectious disease, research and information on COVID-19 are updated rapidly. Therefore, guidelines should be carefully selected for forensic identification. In addition to the above aspects, this paper has also discussed other common issues during the forensic autopsy of patients who died of infectious diseases, such as professional ethics, informed consent, insurance claims, and environmental protection.